Analisis Potensi Kejahatan di Dalam Dunia Maya Terkait Data - Ni Putu Suci Meinarni; Happy Budyana Sari (Kertha Wicaksana, 2020)
This study aims to reveal how the concept of ethics in cyberspace and analyze crimes that occur in cyberspace related to data usage. This research is a type of empirical normative research using diagnostic and prescriptive method approaches. The analysis shows that the first circulation of data contained in cyberspace has the potential for crime because it can be used without the permission of the owner of the data and the acquisition of that data can be done through various methods with an internet connection. Second, the digital data contained in one's gadget will never be safe as long as the data is connected to the internet. Therefore, the community must have an awareness of the digital data they have by not carelessly storing confidential data in their gadgets respectively